Study on the Synthesis, Surface Activity, and Self-Assembly Behavior of Anionic Non-Ionic Gemini Surfactants - Zhiqiang Man; Wenxiang Wu (Molecules, 2024)
The use of surfactants in oil recovery can effectively improve crude oil recovery rate. Due to the enhanced salt and temperature resistance of surfactant molecules by non-ionic chain segments, anionic groups have good emulsifying stability. Currently, there are many studies on anionic non-ionic surfactants for oil recovery in China, but there is relatively little systematic research on introducing EOs into hydrophobic alkyl chains, especially on their self-assembly behavior. This article proposes a simple and effective synthesis method, using 3-aminopropane sulfonic acid, fatty alcohol polyoxyethylene ether, and epichlorohydrin as raw materials, to insert EO into hydrophobic alkyl chains and synthesize a series of new anionic non-ionic Gemini surfactants (CnEO-5, n = 8, 12, 16). The surface activity, thermodynamic properties, and self-assembly behavior of these surfactants were systematically studied through surface tension, conductivity, steady-state fluorescence probes, transmission electron microscopy, and molecular dynamics simulations. The surface tension test results show that CnEO-5 has high surface activity and is higher than traditional single chain surfactants and structurally similar anionic non-ionic Gemini surfactants. Additionally, thermodynamic parameters (e.g., ΔG°mic ΔH°mic ΔS°mic et al. indicate that CnEO-5 molecules are exothermic and spontaneous during the micellization process. DLS, p-values, and TEM results indicate that anionic non-ionic Gemini surfactants with shorter hydrophobic chains (such as C8EO-5) tend to form larger vesicles in aqueous solutions, which are formed in a tail to tail and staggered manner; Negative non-ionic Gemini surfactants with longer hydrophobic chains (such as C12EO-5, C16EO-5) tend to form small micelles. The test results indicate that CnEO-5 anionic non-ionic Gemini surfactants have certain application prospects in improving crude oil recovery.